Impacts of the Xisha topography on the far-field internal solitary waves - Chen, Hanyu; Xu, Andi; Huang, Hao; Li, Delei; Li, Chongyue; Chen, Xueen (Frontiers in Marine Science, 2025)
Xisha sea area features rough bathymetry and complex hydrological environment, acting as an important baroclinic source and sink in the northwestern South China Sea. To investigate the impacts of Xisha topography on the local generation of internal solitary waves (ISWs) and on the propagation of the far-field ISWs, an idealized 2D non-hydrostatic model ORCTM with a very-high resolution was employed to reveal the mechanisms. The result of this study shows that the shallow-water sill of the Xisha Islands, i.e., seamount Panshi-Yu, can generate first- and second-mode ISWs through the internal tidal beam mechanism, as well as second-mode ISWs via the lee-wave mechanism. As is reported previously, Zhongsha Islands could be a far-field source for ISWs in the Xisha sea area. While approaching the shallow-water sill of the Xisha Islands, those far-field first-mode ISWs undergo amplitude reduction and significant phase shift because of their collision with local generated ISWs in the Xisha sea area, while their phase speed increases and decreases due to the increase and decrease of the water depth, respectively. Finally, the far-field ISWs convert into second-mode convex ISWs over the shallow-water sill of the Xisha Islands. This study suggests that rough topography is crucial in the formation of the complicated multimodal internal wave field in the Xisha sea area.